2013
DOI: 10.1159/000353880
|View full text |Cite
|
Sign up to set email alerts
|

Individual Genetic Variations Related to Satiety and Appetite Control Increase Risk of Obesity in Preschool-Age Children in the STRONG Kids Program

Abstract: Background/Aims: The burden of the childhood obesity epidemic is well recognized; nevertheless, the genetic markers and gene-environment interactions associated with the development of common obesity are still unknown. In this study, candidate genes associated to satiety and appetite control pathways with obesity-related traits were tested in Caucasian preschoolers from the STRONG Kids project. Methods: Eight genetic variants in genes related to obesity (BDNF, LEPR, FTO, PCSK1, POMC, TUB, LEP, and MC4R) were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Although there is evidence in the literature for the role of MC4R , GNPDA2 , ADCY3/POMC , SCG3 , BBS4 , TUB , FTO , and SH2B1 in regulating appetite and/or satiety, we did not observe an association of SNPs in or near these genes with the eating behaviors . Again, this may be due to the relatively small sample size of our population.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Although there is evidence in the literature for the role of MC4R , GNPDA2 , ADCY3/POMC , SCG3 , BBS4 , TUB , FTO , and SH2B1 in regulating appetite and/or satiety, we did not observe an association of SNPs in or near these genes with the eating behaviors . Again, this may be due to the relatively small sample size of our population.…”
Section: Discussioncontrasting
confidence: 89%
“…In the previous GWAS paper, a manual literature search was performed into the potential roles of all genes within a region of 500 kb on either side (1 Mb total) of the 97 SNPs found to be associated with adult BMI . This showed that eight genes may play a role in appetite and satiety control . An additional literature search showed that FTO and BDNF may also play a role in appetite and satiety control, providing a total of 10 SNPs to test separately .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubes were then placed into a storage box, which was placed into a sealable bag and stored in their home freezer (−20°C) until being picked up by the research staff. In addition, at the 6-wk visit, saliva samples were collected from both the mother and infant (18). However, in some cases insufficient amounts of saliva were obtained from the infant at 6 wk of age.…”
Section: Methodsmentioning
confidence: 99%
“…At the cellular level, variations in the maternal and child's genetic makeup as well as child and maternal microbiome are being examined using 16S ribosomal RNA sequencing and whole genome shotgun sequencing. Previous reports by our team have identified that candidate gene single nucleotide polymorphisms (SNPs) previously associated with an increased risk of overweight and obesity in adults (16, 17) also were associated with BMI in 2- to 3-y-olds (18). In the SK2 program, how route of delivery, maternal and child diet, maternal and child weight, and child growth trajectories affect the microbiome beginning at birth are being investigated.…”
Section: Theoretical Foundationmentioning
confidence: 99%